2013
DOI: 10.1107/s0909049513020785
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of human CK2α at 1.06 Å resolution

Abstract: The Ser/Thr kinase CK2 consists of two catalytic subunits (CK2 ) and a dimer of the regulatory subunits (CK2 ), and is a ubiquitous enzyme that regulates growth, proliferation and the survival of cells. CK2 is a remarkable drug target for potentially treating a wide variety of tumours and glomerulonephritis. The purified CK2 protein was crystallized using ethylene glycol as a precipitant. The crystal structure of CK2 with 21 loci of alternative conformations, including a niacin, 19 ethylene glycols and 346 wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…This cryptic site was then used to develop a new CK2 α inhibitor with high nanomolar affinity [41]. Interestingly, in one structure of CK2 α (PDB ID 3WAR), it was observed that two ethylene glycol molecules were bound at the entrance of the partially opened α D pocket [41, 42] further supporting our concept of using small glycols to identify cryptic sites in protein targets leaving to the use the identified cryptic sites for drug-design purposes. Another crystallography study of protein CK2 α [42] has shown several ethylene glycol molecules occupying physiologically significant sites of CK2 α suggesting their use in computational methods for binding site determination.…”
Section: Discussionmentioning
confidence: 99%
“…This cryptic site was then used to develop a new CK2 α inhibitor with high nanomolar affinity [41]. Interestingly, in one structure of CK2 α (PDB ID 3WAR), it was observed that two ethylene glycol molecules were bound at the entrance of the partially opened α D pocket [41, 42] further supporting our concept of using small glycols to identify cryptic sites in protein targets leaving to the use the identified cryptic sites for drug-design purposes. Another crystallography study of protein CK2 α [42] has shown several ethylene glycol molecules occupying physiologically significant sites of CK2 α suggesting their use in computational methods for binding site determination.…”
Section: Discussionmentioning
confidence: 99%
“…The internal variance in strongly binding ligands of ~10 kJ/mol (TBBt, 4,5,6-Br 3 Bt, 5,6-Br 2 Bt, 5-BrBt, and most likely 4,5,7-Br 3 Bt) must consequently be attributed to other types of specific ligand-protein interactions, including the eventual contribution of halogen bonding observed in the crystal structure of TBBt bound to maize CK2α [36]. bound to maize CK2α (PDB: 1j91 [57]) and the highest-resolution structures of human CK2α (PDB: 3at2 [82], 3bqc [83], 3h30 [84], 3nsz [85], 3pe1 [86], 3war [87], 4kwp [88]). .…”
Section: Discussionmentioning
confidence: 99%
“…The ensemble of seven structures was modeled by homology, based on the highestresolution structures of human CK2α found in the Protein Data Bank (PDB: 3at2 [82], 3bqc [83], 3h30 [84], 3nsz [85], 3pe1 [86], 3war [87], 4kwp [88]). Each was then structurally aligned with the complex of TBBt with maize CK2α (PDB: 1j91 [57]), using the Mustang algorithm [89] implemented in the Yasara Structure Package [90].…”
Section: Molecular Modeling Of the Complex Of Tbbt With Human Ck2αmentioning
confidence: 99%
“…Recent structural insights of CK2α, CK2β and CK2 (quaternary structure of CK2) gave further knowledge to perform tailor-made compounds. [9][10][11] Thus CK2 is becoming an important drug target for the 21 st century as mentioned by E.G. Krebs in 1999.…”
Section: Introductionmentioning
confidence: 98%